Sex composition of beluga (Husu huso Linnaeus, 1754) along the Iranian coastal waters, Caspian Sea - Moghim, M.; Kor, D.; Bagherzadeh, F.; Taleshian, H.; Tavakoli, M. (2008)
Beluga Huso huso is commercially an important species of sturgeon fish in the Caspian Sea. We determined the sex ratio of the commercial catch of the fish along the Iran coastal waters of the Caspian Sea during the years 1990-2003. Females dominated the catch and composed between 6040% of the landed fish. Observations on gonads maturity showed that immature females decreased from 71% to 47% of total catch. Female fish ratio increased from west to east in the coastal waters.